Productive performance of dairy cows fed with hydrolyzed sugarcane - Donizeti Teixeira Junior (Ciência Rural, 2015)
This study aimed to evaluate the productive performance of dairy cows fed with sugarcane treated with 5g kg-1 of calcium oxide (CaO) or hydroxide [Ca(OH)2]. Eight Holstein cows with 638.01±12.52kg of body weight and milk yield of 20.32±1.5kg d-1 were randomly assigned into two 4x4 Latin squares, fed with the following diets composed of corn silage (CS), fresh sugarcane (FS), sugarcane treated with calcium oxide (STCO) or calcium hydroxide (STCH) as only forage. Data collection lasted five days, after 15 days of adaptation to diets and facilities. The dry matter intake (% of body weight) was higher in diets with CS (3.08) compared to those with FS (2.67), STCO (2.73) or STCH (2.73), which did not differ. Diets with CS determined milk production adjusted for 4% fat (20.05kg d-1) similar to diets containing STCO and STCH (18.01 and 17.89kg d-1, respectively) and higher than those with FS (17.33kg d-1). The experimental diets did not alter the composition of milk. The use of sugarcane treated with Ca(OH)2 is a viable option for feeding Holstein cows with average genetic potential for milk production because it allows production and composition similar to milk dairy cows fed with corn silage, besides benefiting the logistics of feeding in the rural properties.